Anticoagulation withdrawal in antiphospholipid syndrome: a retrospective matched-control study. (March 2018) - Yelnik, C M; Urbanski, G; Drumez, E; Caron, C; Maillard, H; Morell-Dubois, S; Dubucquoi, S; Launay, D; Hachulla, E; Hatron, P Y; Duhamel, A; Lambert, M
Background/Purpose: Long-term anticoagulation is the standard treatment for thrombotic antiphospholipid syndrome (APS). However, in daily practice, the question of withdrawing anticoagulation may arise, without any evidence-based recommendations. This study aimed to assess outcomes in APS patients after anticoagulation withdrawal. Methods: Thrombotic APS patients followed in our centre, whose anticoagulation was withdrawn after APS diagnosis, were retrospectively selected, and were match-controlled with patients under anticoagulation, based on sex, age, APS clinical phenotype and disease duration. Results: Thirty cases with anticoagulation withdrawal were included. Median follow-up was 51 months (12–124). The risk of thrombotic relapse was higher in cases compared to controls (7.3% versus 1.5% patient-year ( p = 0.01 ); hazard ratio 4.8; 95% confidence interval (1.4–16.7)). Male gender, anti-β2GP1 and triple positivity at inclusion were predictive factors for thrombotic relapse. Conversely, aspirin prescription was a protective factor against relapses. Persistence of LA, anti-β2GP1 and triple positivity over time were associated with a higher risk of thrombosis and aPL disappearance with a lower risk. Conclusion: In our study, anticoagulation withdrawal was associated with an increased risk of thrombotic relapse. Our findings emphasize the influence of anti-β2GP1 and triple positivity persistence over time on the risk of relapse and the benefit of aspirin prescription when anticoagulation has been withdrawn.